45% Cell Efficiency in DMFCs via Process Engineering. Issue 4 (3rd August 2020) - Glüsen, A.; Müller, M.; Stolten, D.
Abstract: Methanol is a convenient liquid fuel for fuel cells, but is not converted as efficiently into electrical energy as hydrogen. This is due to the slower reaction of methanol at the anode as well as to methanol permeation. When optimizing the direct methanol fuel cell (DMFC) process, methanol concentration and flow rate, current density and air flow rate must also be taken into account. A high methanol concentration facilitates dynamic operation up to high current densities, but also leads to high methanol permeation. The air flow rate must be adjusted so that the cooling effect of evaporating water is balanced by the heat produced in the cell. Therefore, a cell with low permeation must be operated at low air flow rates to achieve autothermal operation at elevated temperatures, which can in turn reduce cell performance. For each current density, there is an optimum amount of methanol feed. In this paper, we show how these effects have to be balanced using air‐flow rates calculated to ensure thermal equilibrium. It is possible to achieve electrical cell efficiencies of up to 44% in a self‐heating DMFC. Another small increase in efficiency can be achieved by using humidified air at the cathode.